Frontal linear scleroderma (en coup de sabre): A case report - (:unkn) unknown (My University, 2006)
En coup de sabre is a type of linear scleroderma which presents on the frontal or frontoparietal scalp. En coup de sabre in children is associated with asymmetric growth and progressive facial disfigurement. The purpose of this report was to present the case of a 4-year-old girl with a 2-year history of en coup de sabre. The clinical presentation and radiographic findings are discussed.
Keywords: Atrophy; En coup de sabre; Linear scleroderma; Malocclusion